PREDICTIVE POTENTIAL OF IL28B GENE IN HCV PATIENTS, RESISTANT TO DACLATASVIR AND SOFOSBUVIR IN KPK POPULATION - Sardar, Sunya; Sardar Muhammad,; Mohsina Haq,; Najib ul Haq,; Khan, Arbab Muhammad Kashif (Journal of Ayub Medical College Abbottabad, 2023)
Background: Recently various combinations of direct acting antivirals (DAAs) have been tried successfully. Sofosbuvir + Daclatasvir combination has been used with promising results. Recently, resistance has been noticed against DAAs. Therefore, polymorphism at particular sites in the interleukin 28B gene are under study to find possible association with resistance. This study was aimed at finding out any association of SNPs rs8099917 and rs12979860 (IL28B gene) with response and resistance to treatment in HCV genotype 3 patients in Khyber Pakhtunkhwa. Methods: This cross sectional, Analytical study was conducted at Gastroenterology/hepatology OPD of Prime Teaching Hospital, Peshawar Medical College. Collected Samples were stored at -20o C in PCR Lab of the College. DNA extraction and genotyping was carried out at BJ Molecular Biology Lab in Rawalpindi. Data was analyzed by using SPSS version 21. Chi-Square Test was used to see the statistically significant differences between rs8099917 T/G and rs12979860 T/C model. Results: In the IL28-B gene, single nucleotide polymorphism at rs12979860 T/C model, we observed that there are 37.5% CC homozygous, 12.5% TT homozygous and 50% CT heterozygous genotypes in resistant patients and 42.85% CC homozygous, 28.57% TT and 28.57% CT genotype in responder group. In rs12979860 T/C model, genotype of IL28-B in the responder and resistant group significantly varies at p-value =0.00572. Conclusion: We conclude that in SNP at rs12979860, CC genotype is associated with clearance of HCV, while CT genotype was more prevalent in the resistant group and associated with chronicity.